2022
DOI: 10.1007/s12098-022-04145-9
|View full text |Cite
|
Sign up to set email alerts
|

Mother-Newborn Care Unit (MNCU) Experience in India: A Paradigm Shift in Care of Small and Sick Newborns

Abstract: While a Cochrane review (2016) showed that kangaroo mother care (KMC) initiated after clinical stabilization reduces mortality by 40%, evidence of the effect of initiating KMC immediately after birth without waiting for babies to become stable was unavailable until recently. This research gap was addressed by a multicountry, randomized, controlled trial co-ordinated by WHO. This trial was conducted in five hospitals in Ghana, India, Malawi, Nigeria, and Tanzania. Implementation of this trial led to development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…While the natural condition is for a newborn infant to stay in close physical contact with their mother after birth, separation is still common when newborns need specialized care [ 2 ]. There is however, an increasing awareness of and evidence for the importance of keeping parents and infants together after birth and integrating medical technology and pharmaceutical treatments with caregiving that ensures parent-infant closeness [ 3 6 ]. The vision of non-separation of the mother-newborn dyad is stressed in the new World Health Organization (WHO) recommendations for care of the preterm or low-birthweight infant and supported by several meta-analyses.…”
Section: Rationale and Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…While the natural condition is for a newborn infant to stay in close physical contact with their mother after birth, separation is still common when newborns need specialized care [ 2 ]. There is however, an increasing awareness of and evidence for the importance of keeping parents and infants together after birth and integrating medical technology and pharmaceutical treatments with caregiving that ensures parent-infant closeness [ 3 6 ]. The vision of non-separation of the mother-newborn dyad is stressed in the new World Health Organization (WHO) recommendations for care of the preterm or low-birthweight infant and supported by several meta-analyses.…”
Section: Rationale and Evidencementioning
confidence: 99%
“…Recently, the immediate KMC Study, a large multinational randomized controlled trial (RCT) in low- and middle-income countries demonstrated a mortality reduction of 25 percent in the group of immediate skin-to-skin contact and non-separation compared to conventional care in very low birth-weight infants [ 6 , 10 ]. Several trials in high-resource settings have demonstrated the benefits of keeping mothers and their infants physically and emotionally close even after very preterm or complicated births.…”
Section: Rationale and Evidencementioning
confidence: 99%
“…KMC entails infant and direct and ongoing skin-to-skin contact between mother and child. It aids in the prevention of growth retardation, the improvement of weight gain, and the reduction of infection [ 25 ]. In neonatal care facilities, unwell and young babies receive treatment in the NICU, which is staffed 24 hours a day, seven days a week [ 26 ].…”
Section: Reviewmentioning
confidence: 99%
“…MNCU is a facility where sick and small neonates are cared for with their mothers, with all facilities of level 2 newborn care and provision for postnatal care to mothers (Mother-Newborn Couplet Care). 3 The mother has her bed inside the Newborn Intensive Care Unit (NICU) and stays there day and night unlike conventional NICUs where mothers visit intermittently. When mother was not available, iKMC was provided by another person (surrogate) designated by the parents.…”
Section: Introductionmentioning
confidence: 99%